PENGARUH QUALITY CONTROL CIRCLE DAN TRUST PADA WORLD CLASS DI PERUSAHAAN MANUFAKTUR KABUPATEN BOGOR - Sri Mulyati; Eki Prafitri Ramadani; Ardila Pratiwi; Pilda Agustin; Mei Candra Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
. In the era of global competition, companies face challenges in maintaining their existence and enhancing competitiveness. This study aims to analyze the influence of quality control circles (QCC) and trust on achieving world-class status at Company X. The research employs a quantitative method using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3 software. Primary data were collected through online questionnaires involving 50 respondents, who are employees of Company X. The results show that QCC has a positive and significant influence on trust (T Statistic = 46.771, p = 0.000). However, quality control circles do not have a significant direct influence on world-class status (T Statistic = 0.248, p = 0.804). Furthermore, trust does not have a significant influence on achieving world-class status (T Statistic = 0.110, p = 0.913) and does not act as an effective mediator in the relationship between QCC and world-class status (T Statistic = 0.107, p = 0.915). In conclusion, although quality control circles can enhance employees' trust in management, trust alone is insufficient to drive the achievement of world-class status.